If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) + -1(x + 2) + 10 = 0 Reorder the terms: 3(-3 + x) + -1(x + 2) + 10 = 0 (-3 * 3 + x * 3) + -1(x + 2) + 10 = 0 (-9 + 3x) + -1(x + 2) + 10 = 0 Reorder the terms: -9 + 3x + -1(2 + x) + 10 = 0 -9 + 3x + (2 * -1 + x * -1) + 10 = 0 -9 + 3x + (-2 + -1x) + 10 = 0 Reorder the terms: -9 + -2 + 10 + 3x + -1x = 0 Combine like terms: -9 + -2 = -11 -11 + 10 + 3x + -1x = 0 Combine like terms: -11 + 10 = -1 -1 + 3x + -1x = 0 Combine like terms: 3x + -1x = 2x -1 + 2x = 0 Solving -1 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5
| f(x)=5x-2+x(-6x+10) | | x-10+x-15=x+15 | | y=5x^2+11x+12 | | 2x+2y=3.25 | | 18-2x= | | f(x)=-9x-2+x(-3x+6) | | 7u=-8u+30 | | 6+5(x-2y)= | | 15+6-4*28= | | 12-5*6= | | 5*23+7-62= | | 3*6-4= | | 3n-4=37 | | 54x-1=27x | | 12x^3+14x-48x=0 | | f(x)=In(x^3)(2x^4+1) | | 9+39+22/11-9+3 | | 2x-5(x-4)=-2+3x+4 | | 2x+9=7x-10 | | 5(n+2)=3/5 | | 1x^3+1x^2+c=0 | | (x-4)^(3/2)=16 | | y=4sinx+5 | | 1/2m=28 | | 9p^2+56=18p | | y=-x^2-5x+9 | | 3+2w=8-w | | 2a^2-6a-56=0 | | 2/3p+8=-4 | | 0=2x^2+2x-48 | | 2b-b=2b | | x+5/2=1-x |